EMPOWERING THE MARGINALIZED: COMMUNITY CENTER AS A PLACE FOR THE EMPOWERMENT OF STREET CHILDREN IN CICENDO DISTRICT, BANDUNG CITY - Zyahrani Herawan, Dwitri
Uncontrolled population growth has caused various problems, such as economic crisis and social inequality. This situation has an impact on a special group in the society, namely the Low Income Community (LIC) group. The environment of children in the LIC family forces them to help their family’s financial problems. These children spend most of their time working on the streets to earn money that can help them to survive. This phenomenon is often found in several big cities in Indonesia. The government tried to reach street children by sending them to shelters, but these facilities were difficult to access and no follow-up that could improve their quality of life. The contribution through architecture that can be done is to create a built environment that can accommodate people of various ages in the form of a community center. The community center is presented in one of the areas with the highest number of street children in Bandung City, one of them is in Cicendo District. This project occupies a land area of about 5,799.4 m² and is located in a residential zone. The building is intended for the public, especially for people who live in Cicendo. The surrounding community can take advantage of the various facilities available in the building and participate in helping the street children. This project aims to provide public space for the community, as well as accommodate facilities and infrastructure that can help improve the quality of life of street children. The design issues of this project are to provide spaces for diverse social activities, facilitate programs to improve knowledge and skills, support economic activities, and accommodate the rehabilitation needs of street children.